Influence of surgical approach on postoperative femoral bone remodelling after cementless total hip arthroplasty - Merle, Christian; Sommer, Julia; Streit, Marcus R.; Waldstein, Wenzel; Bruckner, Thomas; Gotterbarm, Tobias (HIP international, 2012)
We retrospectively evaluated the femoral periprosthetic bone mineral density (BMD) in a consecutive series of patients who had undergone total hip arthroplasty (THA) with a straight, double tapered cementless stem using a muscle-sparing anterolateral (group A) and the transgluteal (group B) surgical approach. Dual-energy x-ray absorptiometry (DXA) measurements were performed in the first postoperative week (t1), and after 3 (t2), 6 (t3) and 12 months (t4) using an identical protocol. Patients were clinically and radiographically evaluated at final follow-up (t4)., A complete set of four consecutive DXA measurements was obtained for 16 hips in group A and 26 hips in group B. In patients in whom the transgluteal approach was used (Group B), we observed a significantly greater decline in overall periprosthetic BMD (netavg) and in BMD in the periprosthetic regions of interest (ROI) 1, 4, 5 and 6 between t1 and t4. At clinical and radiographic evaluation at t4, no differences between the groups were detected., Femoral periprosthetic BMD is affected by the selected surgical approach in the first postoperative year. This might be attributed to altered femoral loading as a result of differences in intraoperative damage to the abductor muscles.